DEVELOPMENT OF LEADERSHIP AND LEADERSHIP SKILLS IN YOUTH - Boltayeva Sh.B.; Zohidov Olmosbek; Rakhmonov Rustam (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article describes the role of leadership and leadership in our lives, its advantages, its difficulties, its role in the economy and how it relates to all areas, the specific characteristics of leadership and leadership in young people.